Il Central Council for research in Unani medicine, Delhi (CCRUM, Ministry of health and family welfare, Government of India). - Fabrizio Speziale (AM. Rivista della Società Italiana di Antropologia Medica, 1999)
Il Central Council for research in Unani medicine, Delhi (CCRUM, Ministry of health and family welfare, Government of India).